Effects of isoflurane and thiopentone in eliminating the fasciculations provoked by succinylcholine in children - Bayar, M.K.; Bestas, A.; Yasar, A.; Erhan, O.L. (My University, 1997)
In this study we have examined 68 children (2-10 years) from ASA I group to investigate the effects of isoflurane and thiopentone in eliminating the muscle fasciculations provoked by succinylcholine in children. The children, who were randomly scheduled for two groups, were given 0.015 mg/kg atropine IM for premedication 60 minutes before the operation. Group I patients were given 3.5 % isoflurane, 70 % N2O, 30 % O2 and 2 mg/kg IV succinylcholine for induction, 5 mg/kg thiopentone, 1.5 mg/kg succinylcholine IV were administered to the patients in group T for this purpose. The fasciculations evolved in these patients were evaluated according to the Cullen scoring. Group I patients were seen to demonstrated fasciculations with a lower frequency and intensity than the Group T (p<0.05). A significant correlation was observed between the fasciculations score and age weights in Group I. In Group T the correlation between age and fasciculations score was found to be significant while an insignificant correlation was noted between the fasciculations score and weight. In both groups no changes in the heart rate were measured before and after the induction. During induction with isoflurane coughing was observed in six children. We can concluded that isoflurane can be used as a safe agents towards eliminating the muscle fasciculations provoked by succinylcholine in children.
COCUKLARDA SUKSINILKOLININ OLUSTURDUGU FASIKULASYONLARA ISOFLURAN VE TIYOPENTONUN ETKILERI
Keywords: Anaesthetics; Complications; Fasciculations; Isoflurane; Succinylcholine